Analysis of Leadership Style and Performance Assessment Towards Work Productivity Case Study: PT KJP (Material Packing Company) - Permadi, Yudhi; Dwianto, Agung Surya (SAFE-Network, 2025)
This study explores the interplay between leadership style and performance appraisal systems and their influence on work productivity within PT KJP, a material packaging company operating under high operational pressure. Utilizing a qualitative case study with a phenomenological approach, data were collected through in-depth interviews, participant observations, and internal document analysis. The findings reveal that a dual leadership style combining transformational and transactional elements is practiced contextually across managerial levels. While transformational leadership enhances employee engagement and motivation, transactional mechanisms are applied for short term efficiency. Furthermore, the study identifies significant gaps in the performance appraisal system, which is perceived by employees as formalistic and lacking developmental value. Transparent and participatory appraisal processes, supported by consistent leadership, were found to positively influence motivation and productivity. The study concludes that an integrated human resource strategy aligning leadership development with feedback-oriented performance evaluations is essential for optimizing productivity. Recommendations are offered for leadership training and redesigning appraisal systems tailored to the operational dynamics of the organization.